2016
DOI: 10.7150/thno.16923
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable Nitrogen-Doped Carbon Nanodots for Non-Invasive Photoacoustic Imaging and Photothermal Therapy

Abstract: Multifunctional nanoparticles have been widely investigated for biomedical applications, such as imaging, therapy, and drug delivery. Especially, photoactive nanoparticles have received great attention as theranostic agents because of their heat-generating abilities after exposure to laser irradiation. However, photostability and safety issues have been the technical hurdles for further clinical applications. Here, we designed nitrogen (N)-doped carbon nanodots (N-CNDs) that have strong absorption in the near-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
84
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 141 publications
(85 citation statements)
references
References 60 publications
1
84
0
Order By: Relevance
“…As promising carbon‐based imaging probes, carbon nanodots (CNDs) have also attracted enough attention because of their excellent water solubility, biocompatibility, and photostability . Kim and co‐workers developed nitrogen (N)‐doped CNDs (N‐CNDs) with an ultrasmall particle size of ≈3 nm, which could be used both as a photoacoustic (PA) contrast agent and a photothermal agent with strong absorption in the near‐infrared (NIR) region ( Figure a–d) . Finally, the biodegradability and renal excretion of N‐CNDs were verified by whole‐body PA imaging and degradation experiments (Figure e,f).…”
Section: Quantum Dotsmentioning
confidence: 99%
See 1 more Smart Citation
“…As promising carbon‐based imaging probes, carbon nanodots (CNDs) have also attracted enough attention because of their excellent water solubility, biocompatibility, and photostability . Kim and co‐workers developed nitrogen (N)‐doped CNDs (N‐CNDs) with an ultrasmall particle size of ≈3 nm, which could be used both as a photoacoustic (PA) contrast agent and a photothermal agent with strong absorption in the near‐infrared (NIR) region ( Figure a–d) . Finally, the biodegradability and renal excretion of N‐CNDs were verified by whole‐body PA imaging and degradation experiments (Figure e,f).…”
Section: Quantum Dotsmentioning
confidence: 99%
“…e,f) Serum biochemistry assay of mice after the injection of N‐CNDs. Reproduced with permission . Copyright 2016, Ivyspring International Publisher.…”
Section: Quantum Dotsmentioning
confidence: 99%
“…The intravenous injection of targeted SWCNTs in mice led to an eightfold increase in the PA signal in the tumor compared to the mice injected with nontargeted SWCNTs ( Figure ). Other carbon‐nanomaterial contrast agents have also been developed, including GO nanoribbons, graphene nanosheets, carbon nanospheres, carbon nanodots, and nanodiamonds . Lalwani et al investigated graphene nanoribbons as contrast agents for PA imaging and showed that oxidized single‐ and multiwalled GO nanoribbons exhibited about 5–10‐fold signal enhancement for PA imaging in comparison with the blood at the wavelength of 755 nm .…”
Section: Biomedical Applicationsmentioning
confidence: 99%
“…Microwave-assisted carbonization PTT 20 mg per kg body weight 808 0.8 10 30 [168] Polythiophene and diphenyl diselenide Hydrothermal PTT 80 µL of 1 mg mL −1 CDs 880 0.5 10 58.2 [163] Polythiophene phenylpropionic acid Hydrothermal PTT 100 µL of 2 mg mL −1 CDs 671 2 10 38.5 [159] Polythiophene benzoic acid Hydrothermal PDT/PTT 100 µL of 2 mg mL −1 CDs 635 2 10 36.2 [169] Citric acid, nitric acid, ethanolamine Pyrolysis PTT 100 µL of 20 mg mL −1 CDs 808 2 10 3.77 [170] EDTA, copper chloride Hydrothermal PDT/PTT 200 µL of 3 mg mL −1 CDs 808 1 10 - [166] Hypocrella bambusae Solvothermal PDT/PTT 200 µL of 2 mg mL −1 CDs 635 0.8 10 27.6 [171] o-Phenylenediamine, l-cysteine Hydrothermal PTT 2 mg kg −1 808 1 10 41.3 [172] It was found that the localized tumor temperature of PDT+PTT treatment group quickly increased to 53.9°C, comparable to the PTT groups (53.5°C). The PDT treatment group experienced negligible temperature increase.…”
Section: Photodynamic Therapymentioning
confidence: 99%